Fermatean Neutrosophic Fuzzy Methodology for Teaching Quality Analysis in University Basketball Training - Yongzhi Wang; Ruifang Li; Mingtao Guo (Neutrosophic Sets and Systems)
University basketball training plays a pivotal role in developing athletes' technical, tactical, and physical skills. Analysis of teaching quality in this context is essential for optimizing training methodologies, enhancing player performance, and ensuring long-term athletic success. This paper explores a structured approach to assessing teaching quality in university basketball training, considering factors such as coaching competence, training design, player engagement, and psychological preparation. The integration of modern performance analysis tools, feedback mechanisms, and facility assessments contributes to a comprehensive evaluation framework. By adopting a multi-dimensional assessment approach, universities can refine their training programs to create a more effective and engaging learning environment for student-athletes. We use multi-criteria decision-making (MCDM) to analysis these different criteria and alternatives. Two MCDM methods are used such as BWM to compute the criteria weights and the EDAS method to rank the alternatives. These methods are used under the Fermatean Neutrosophic Fuzzy sets to deal with uncertainty information. The sensitivity analysis is applied to show the stability of the ranks.